Neil Bernstein letter to James J. Dinsmore regarding summer bird sightings in northwest Iowa, June 24, 1997 - Bernstein, Neilet al (1997)
Letter from Neil Bernstein to James J. Dinsmore regarding summer bird sightings, June 24, 1997. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of summer 1997. Epson - sheet feed